Sentralisasi Manajemen Hotspot Menggunakan Transparent Bridge Tunnel EoIP over SSTP - I Putu Hariyadi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2017)
STMIK Bumigora is the first computer college in the province of West Nusa Tenggara (NTB). There are 11 hotspots spread across the campus to provide Internet services through a wireless connection for the academic community. The increasing number of hotspots that must be managed with locations scattered in various Mikrotik routers hence make the process of management and monitoring hotspots become complex, ineffective and efficient. Centralized campus hotspot management using a transparent bridge EoIP over SSTP can help solve the problems at hand. Ethernet over IP (EoIP) Tunneling is a Mikrotik RouterOS protocol that creates an Ethernet tunnel between routers over IP connections. EoIP tunnel built on SSTP tunnel (EoIP over SSTP) with Site-to-Site type. SSTP is a new form of Virtual Private Network (VPN) tunnel that provides a mechanism for encapsulating Point-toPoint Protocol (PPP) traffic through the SSL path of the HTTPS protocol. The IP address of the SSTP interface is used as the local reference and remote address of the EoIP over SSTP tunnel. The application of bridging on EoIP interfaces and interfaces connected to Access Point devices forms a logical network so that the management and monitoring of hotspot services can be performed centrally on one router.